Pengaruh Edukasi Terhadap Tingkat Pengetahuan Ibu-Ibu PKK Tentang Sadari Di Desa Sei Buluh Kecamatan Teluk Mengkudu Kab Serdang Bedagai - Hasibuan, Hesty Romauli; Simanullang, Rostime Hermayerni (Indonesian Trust Nursing Journal, 2024)
Breast cancer is a malignant disease due to abnormal cell growth and development in women. The development of breast cancer in the sufferer's body takes a long time and the risk factors that play a role are very diverse. This is the magnitude of the health problem of breast cancer and the consequences it causes, so it is necessary to intervene/practice public health in counseling or education, one of the important things in overcoming breast cancer is breast self-examination which can be done early by women. The purpose of this study was to determine the effect of education on the level of knowledge of PKK women about BSE in Sei Buluh Village, Teluk Mengkudu District, Serdang Bedagai Regency. The research method is pre-experimental pre & post without control. A sample of 38 PKKwomen in Sei Buluh Village participated in this study using the Incidental Sampling technique. The researcher conducted further education and data collection using the Education instrument on the Level of Knowledge of PKK women in Sei Buluh Village, Teluk Mengkudu District, Serdang Bedagai Regency before and after using the Wilcoxon Rank Test analysis. Statistical test results using the Wilcoxon Rank Test Based on the results of the study, it was found that the knowledge of PKK women in Sei Buluh Village before being given education was lacking as many as 23 people (60.5%) and the knowledge of PKK women in Sei Buluh Village after being given education was sufficient as many as 25 people (65.8%). The results of the Wilcoxon Test obtained a p value of 0.000 or <0.05. Thismeans that it can be concluded that there is an Effect of Education on the Level of Knowledge of PKK women in Sei Buluh Village.